Impact of Sacubitril/Valsartan on surfactant binding proteins, central sleep apneas, lung function tests and heart failure biomarkers: Hemodynamic or pleiotropism? - Mapelli, Massimo; Mattavelli, Irene; Salvioni, Elisabetta; Banfi, Cristina; Ghilardi, Stefania; De Martino, Fabiana; Gugliandolo, Paola; Mantegazza, Valentina; Volpato, Valentina; Basile, Christian; Branco Pires, Maria Inês Fiuza; Sassi, Valentina; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Little is known about the mechanism underlying Sacubitril/Valsartan effects in patients with heart failure (HFrEF). Aim of the study is to assess hemodynamic vs. non-hemodynamic Sacubitril/Valsartan effects by analyzing several biological and functional parameters. Methods: Seventy-nine patients (86% males, age 66±10 years) were enrolled. At baseline and 6 months after reaching the maximum Sacubitril/Valsartan tolerated dose, we assessed biomarkers, transthoracic echocardiography, polysomnography, spirometry, and carbon monoxide diffusing capacity of the lung (DLCO). Results: Mean follow-up was 8.7±1.4 months with 83% of patients reaching Sacubitril/Valsartan maximum dose (97/103mg b.i.d). Significant improvements were observed in cardiac performance and biomarkers: left ventricular ejection fraction increased (31±5 vs. 37±9 %; p<0.001), end-diastolic and end-systolic volumes decreased; NT-proBNP decreased (1196 [IQR 648-2891] vs. 958 [IQR 424-1663] pg/ml; p<0.001) in parallel with interleukin ST-2 (28.4 [IQR 19.4-36.6] vs. 20.4 [IQR 15.1-29.2] ng/ml; p<0.001) and circulating surfactant binding proteins (proSP-B: 58.43 [IQR 40.42-84.23] vs. 50.36 [IQR 37.16-69.54] AU; p=0.014 and SP-D: 102.17 [IQR 62.85-175.34] vs. 77.64 [IQR 53.55-144.70] AU; p<0.001). Forced expiratory volume in 1 second and forced vital capacity improved. DLCO increased in the patients’ subgroup (n=39) with impaired baseline values (from 65.3±10.8 to 70.3±15.9 %predicted; p=0.013). We also observed a significant reduction in central sleep apneas (CSA). Conclusion: Sacubitril/Valsartan effects share a double pathway: hemodynamic and systemic. The first is evidenced by NT-proBNP, proSP-B, lung mechanics, and CSA improvement. The latter is confirmed by an amelioration of DLCO, ST-2, SP-D as well as by reverse remodeling echocardiographic parameters.